Arising issues due to the inconsistency between the Pertis braille Quran text and the Mushaf al-Madinah text - Rasdi, Mohd Nur Adzam; Abdul Aziz, Nur Atiqah; Jaafar, Noornajihan; Mohamed, Khairul Anuar; Sharuddin, Saiful Azri (2023)
This qualitative research aims to explore the issues arising from the discrepancy between the Quran Braille (PERTIS) and Mushaf al-Madinah texts, focusing on the perspective of visually impaired individuals who are primary users of the Braille Quran. Through interviews as the data collection method, seven participants were carefully selected based on their relevance to the research objectives. By using Nvivo 8.0 as an analytical instrument, the findings reveal two significant issues stemming from the inconsistency between the PERTIS Braille Quran and the Mushaf al-Madinah texts. Visually impaired individuals encounter challenges during inclusive activities, such as Quran learning and recitation with sighted individuals. Additionally, the misalignment calls for the adoption of distinct learning methods and strategies that cater to their abilities and the unique Braille writing system. In conclusion, addressing these disparities is crucial to foster inclusive Quranic education and activities, enabling visually impaired individuals to engage effectively in Quranic learning and recitation alongside sighted peers.